Решите уравнение: a) 6,3-3,6x= -2,9x б)-3(x+9)=4x+8.

Решите уравнение: a) 6,3-3,6x= -2,9x б)-3(x+9)=4x+8.
Гость
Ответ(ы) на вопрос:
Гость
а) 6,3-3,6 х=-2,9 х -3,6 х +2,9 х=-6,3 -0,7 х=-6,3 х=9 б) -3(х+9)=4 х+8 -3 х-27=4 х+8 -3 х-4 х=8+27 -7 х=35 х=-5
Гость
а) 6,3 - 3,6х = -2,9х                  б) -3(x+9) = 4x+8     6,3 = 3,6х - 2,9х                        -3x - 27 = 4x + 8      0,7х = 6,3                                    -7x = 35              х = 9                                         x = - 35 : 7                                                           x = - 5 Проверка:                                Проверка:      6,3 - 3,6*9 = -2,9*9                  -3(-5+9) = -5*4 + 8        6,3 - 32,4 = -26,1                           -12 = -12               -26,1 = -26,1         Ответ: {9}                                  Ответ: {-5}
Не нашли ответ?
Ответить на вопрос
Похожие вопросы